Readability of corporate annual reports of top 100 Malaysian companies - Mohamad, Rosli; Abdul Rahman, Azhar (Universiti Utara Malaysia, 2006)
The main purpose of this paper is to compare the readability of two narrative sections in Malaysian corporate annual reports. Further more the authors invertigate whether readability of one sections reflects the readability of another section. On top of that, consistency of the readability level across companies is also reviewed. The study assess the readability of the chairman's statement and notes to the accounts of top 100 Malaysian corporate using Flesch readability formula. Overall results indicated consistent finding with prior studies consistent finding with prior studies with which the readability of both narratives is considered as very difficult to read. Specifically, the findings revealed that the management does not present the chairman's statement in a more readable style despite greater flexibility offered in its presentation than notes to the accounts. Further test also confirmed that a readable chairman's statements is not necessarily followed by readable notes to the accounts and vice versa. Finally, The study reported that readability of notes to the accounts is more consistent among companies than the chairman's the chairman's statement. It is therefore recommended that the management should consider presenting the chairman's statement in a plain English to ensure that investors accurately receive the conveyed massage.